Adaptasi dan uji properti psikometrik The PERMA-Profiler pada orang Indonesia - Elfida, Diana; Milla, Mirra Noor; Mansoer, Winarini Wilman D.; Takwin, Bagus (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractThe PERMA-Profiler is a well-being instrument which combines the hedonic and eudaimonic perspective of well-being. This instrument was developed based on well-being theory (Seligman, 2012) which explained well-being as a multidimensional construct, included positive emotion, engagement, relationship, meaning, and accomplishment (PERMA). This study aimed to adapt and examine the psychometric properties of the PERMA-Profiler in Indonesian people. The participants were 439 Indonesians, aged 17-63 years old (mean age = 30,82; SD = 10,00). Confirmatory Factor Analysis (CFA) was used to test the measurement model of PERMA. The result showed that the PERMA-Profiler met the goodness of fit criteria as a multi dimensional construct with five elements. Fourteen items have satisfactory factor loading. The PERMA-Profiler has good construct reliability as well as Cronbach’s alpha. The convergent validity was shown by the positive correlation between elements of PERMA with satisfaction with life scale (SWLS) and subjective happiness scale (SHS). In addition, the significant correlation between elements and each element with a total score proved the multidimensional nature of PERMA. The overall findings showed that the adaptation version of PERMA-Profiler have a good psychometric property and could be applied to Indonesian people.Keywords: confirmatory factor analysis; PERMA; reliability; validity; well-being AbstrakThe PERMA-Profiler merupakan instrumen kebahagiaan yang memadukan perspektif hedonik dan eudaimonik untuk mengukur kebahagiaan. Instrumen ini mengacu pada well-being theory (M. E. P. Seligman, 2012) yang menjelaskan kebahagiaan sebagai konstruk multidimensi, meliputi positive emotion, engagement, relationship, meaning, dan accomplishment (PERMA). Penelitian ini bertujuan untuk mengadaptasi dan menguji properti psikometrik the PERMA-Profiler pada orang Indonesia. Partisipan berjumlah 439 orang Indonesia (pria = 108, wanita = 331) dan berusia antara 17- 63 tahun (usia rerata = 30,82 tahun; SD = 10,00). Confirmatory Factor Analysis (CFA) digunakan untuk menguji model pengukuran. Hasil CFA memperlihatkan the PERMA-Profiler memenuhi kriteria kecocokan model sebagai konstruk multidimensi yang terdiri dari lima elemen. Terdapat 14 dari 15 aitem yang valid. Keempatbelas aitem juga yang mengukur satu konstruk tunggal yaitu well-being. The PERMA-Profiler juga memperlihatkan reliabilitas komposit dan konsistensi internal yang memuaskan. Korelasi positif yang signifikan dengan pengukuran skala kepuasan hidup dan skala kebahagiaan umum menunjukkan PERMA-Profiler memenuhi validitas konvergen. Setiap dimensi berkorelasi signifikan satu sama lain dan dengan skor total. Temuan ini memperlihatkan hasil adaptasi the PERMA-Profiler memiliki properti psikometrik yang bagus dan dapat diterapkan pada orang Indonesia.Kata Kunci: confirmatory factor analysis; kebahagiaan; PERMA; reliabilitas; validitas